Archean Rocks of the Diorite Window Block in the Southern Framing of the Monchegorsk (2.5 Ga) Layered Mafic-Ultramafic Complex (Kola Peninsula, Russia) - Pavel Pripachkin; Tatiana Rundkvist; Nikolay Groshev; Aiya Bazai; Pavel Serov (Minerals, 2020)
The intermediate rocks classified as diorite-gneisses occur within the southern part of the Monchegorsk (2.5 Ga) layered mafic-ultramafic complex (Kola Peninsula, Russia). These diorite-gneisses belong to a block historically known as the diorite window (DW) block. The same rocks occur in a framing of the Monchegorsk complex. The DW block is predominantly composed of diorite-gneisses and, to a lesser degree, of amphibolites. Multi-ordinal banding, complex folding, boudinage and metamorphic transformations, garnet porphyroblasts, and tourmaline veinlets are typical of the diorite-gneisses. In accordance with the U-Pb isotope data, the age of the diorite-gneisses in the DW block is 2736.0 ± 4.6 Ma. The Sm-Nd mineral (garnet, biotite, and tourmaline) isochron for the DW rocks has yielded an age of 1806 ± 23 Ma (related to the processes of the Svecofennian orogeny). The DW diorite-gneisses are compared with the metadiorites of the Gabbro-10 massif. The latter is a part of the Monchegorsk complex, with U-Pb crystallization age of 2498 ± 6 Ma. On the basis of geological and isotope-geochemical data, it is shown that the DW rocks belong to the Archean basement while the Gabbro-10 metadiorites probably represent one of the late-magmatic phases of the Monchegorsk complex.